Conflitos na pesca da lagosta e suas implicações sobre a saúde, o trabalho e o ambiente - Costa, Francinete Pereira da (2019)
The relations between work, health and economy are present in all social contexts and new communication programs with the emergence of new elements that interfere in the leadership relationship, directly affecting the population's health-disease process. The fishing work scenario is no different: from the moment the predatory fishing work is introduced in the territories, artisanal fishing is an unbalanced environment, there is no work and, consequently, on workers' health. This reality is perceived in Praia de Redonda, Icapuí-Ce, which is a community of artisanal fishermen who experience conflicts in lobster fishing with fishermen who carry out predatory fishing, as these had their mode of production influenced by modern capitalist technologies with repercussions on the work process and nature. In this scenario, lobster fishing is currently in decline due to the enormous pressure that predatory fishing exerts on these stocks, causing a difficult bioecological and socioeconomic problem. The study aims to analyze the repercussions of the conflict on lobster fishing on health, work and environment in the context of artisanal fishermen of Redonda beach, Icapuí-Ce. Therefore, this research used the focus group and semi-structured interview techniques for data collection. Data analysis was performed through content analysis. The survey participants were artisanal fishers from the community of Redonda, as well as leaders involved in community fisheries issues. The results show that there have been significant changes in the artisanal fishing community and work process resulting from the conflict with predatory fishing, such as: in the health-disease process the changes are due to the fact that fishermen associate the lack of health through the lack of conditions to perform their work activity, where the feeling of sadness (which can affect diseases such as depression, alcoholism, among others) was elucidated due to the fact that they are unable to support their families and the accumulation of debts, as well as the consequences of their own activity labor. As for the work category, fishermen recognize various changes through conflicts in fishing, such as: the gradual disappearance of the figure of the master at the time of technological advancement; the migration of fishermen to other cities and regions in search of a fuller fishing season; the need to perform other work tasks to supplement family income, a fact that gradually distances the fisherman from the marine environment. In the environment category, the perceived changes were the pollution of lobsters and the marine environment due to contact with chemicals derived from iron drums used by predatory fishing as lobster attractions; the marked scarcity of the crustacean due to overexploitation of the species.